Feasibility study of a pedestrianisation scheme in Klang town volume I "planning and design" / Ahmad Zimy Ahmad Shukri - Ahmad Shukri, Ahmad Zimy (1992)
The principle aim of traffic management when implemented is to minimise the use of the existing streets system and improve road safety, without impairing enviromental quality. The type of schemes usually of short term and low capital cost improvement. The scheme involves the management measures which may be related to a single traffic category, such as pedestrians or to mixed traffic. This research was a case study on a feasibility of a pedestrianisation schemes in Klang town. The existing road network system and traffic management schemes which have already been implemented were studied in relation to the activities involved in the central business district ( CBDs ), a suitable area or areas for the schemes were identified and comprehensive design for the system proposed. Social and economic evaluations, prediction and assessments were carried out to justify for the economic and enviromental impact to the affectad areas. This part of the report was presented in volume two of the study.